"We are children like others": Pathways to mental health and healing for children born of genocidal rape in Rwanda. (June 2019) - Kahn, Sarilee; Denov, Myriam
Despite the well-documented prevalence of rape as a strategy of war, little is known about the specific psychological consequences to children born of conflict-related sexual violence. The results of data analysis of 7 focus groups and 60 in-depth interviews with children born of genocidal rape in Rwanda indicated that they are carrying the trauma of their own stigmatization and marginalization, are burdened with their mothers' trauma, and, we conclude, symbolize unresolved collective trauma for the society. Analysis also reveals that healing for these young adults requires interpersonal and intrapersonal compassion and acceptance, a meaningful connection with a peer group, societal recognition, and empowerment to help contribute to and transform their lives and societies. Each of these pathways to healing—intrapersonal, interpersonal, and social—is contingent upon the other, and none can be considered in isolation. To support this largely invisible population striving to fulfill their potential, opportunities need to be created for self-acceptance and acceptance by mothers, families, and communities; sharing and building emotional and social bonds with their cohort group; formal recognition; official social rituals to validate their experiences and those of the mother–child dyad in the context of culture and community; and for socioeconomic opportunities to enable them to fully participate in building the future of Rwanda.